PENERAPAN METODE DEMPSTER SHAPER DALAM MENDIAGNOSA PENYAKIT MENINGITIS PADA BALITA MENGGUNAKAN FRAMEWORK ANGULAR - Rusdin Halomoan Hsb; Suendri Suendri; M Fakhriza (JISTech (Journal of Islamic Science and Technology), 2021)
Meningitis must be detected as soon as possible, just like any other disease, to give the patient the best chance of recovery. Physical examination, symptoms, what is felt, and the suspected tissue particles are all used to establish the diagnosis of Meningitis. If anything unusual happens, we should consult with specialists who are experts in their field to check the facts and situation. However, some people are more sedentary because they don't know how to treat their illness, or because they believe it's just a symptom of a common illness, or because it's expensive to see a doctor. The lack of public awareness in the field of meningitis, as well as the lack of professionals in the field, makes it difficult to treat people with this disease. Given these circumstances, having a Meningitis detection application system that uses the Dempster Shafer technique to diagnose the type of Meningitis disease based on clinical symptoms is very important. The Dempster Shafer approach will be used to create an expert system application, where the results of previous expert system trials including patient symptoms reveal that this system is capable of diagnosing disease based on symptoms, even when the perceived symptoms are ambiguous. To find out the symptoms experienced by the patient. The application will then inform the public about the symptoms experienced by the patient